The One Health national policy network to combat antimicrobial resistance in Senegal - Léo Delpy; Mouhamadou Moustapha Sow; Mamadou Ciss; Assane Gueye Fall; Marion Bordier (Health Policy and Planning, 2026)
Abstract Antimicrobial resistance (AMR) is a health threat globally and particularly in low- and middle-income countries. Senegal, like many other African countries, faces significant challenges in addressing the AMR crisis. This article aims to investigate the policy-making process that supports efforts to combat AMR in Senegal since the adoption of the country’s 2017 National Multisectoral Action Plan Against Antimicrobial Resistance. A survey was conducted between January and August 2023 with key organizations involved in the policy-making process related to AMR at the national level. We collected both quantitative data describing the policy networks and qualitative data characterizing the beliefs of organizations. These mixed data were analysed using a dual approach, employing the policy network analysis and the advocacy coalition framework, to investigate the complexity of the national policy-making process. This article provides empirical evidence that the policy network has a centre-periphery structure, with a coalition of three organizations at its heart. Additionally, this article highlights the importance of technical and financial partners in the process of making policies to combat AMR in Senegal.